An analysis: Internet slang usage as code-switching in X (Twitter) - Bertha Resivia Gayatri; Irwan Fathur Rosyid; Lely Tri Wijayanti (Universitas Merdeka Malang, 2023)
This study aimed to identify the types of internet slang used by X users as code-switching and investigate the users’ reasons for using them in their tweets. The results of this study are expected to contribute to the readers ' internet slang, such as code-switching, which is often used to communicate through X (Twitter), and to know the reasons users use slang in their tweets on Twitter. The study is qualitative, with the first data collected from Twitter. The respondents of this studyare 20 male and female active users of Twitter. The second data was collected using questionnaires. The sample was selected by purposive sampling method from different ages. The results suggest that a variety of Internet slang mostly used by X users as code-switching are capitalizations and other symbols, generated emoticons and smileys, intentional misspellings, Letter homophones, also letter repetition. There are some reasons X users use slang as code-switching in their tweets, such as to make it fresher and more personal, to playfulness or waggishness, to ease social interaction, and also to make it secret.